AGRARIAN RESOURCES BASED LEADERSHIP TRAINING FOR PUCUNG VILLAGE GOVERNMENT OFFICE STAFF - Aristiono Nugroho (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
After having the Masterplan, the Pucung Village Government needs outreach and community awareness activities about important points in the master plan, which are packaged in an activity entitled: "Agrarian Resource-Based Leadership Training for Pucung Village Government Office Staff." This study uses qualitative research methods, with a rationalistic approach. The number of informants was 21 people, who were selected purposively. The data consists of: (1) Primary data, obtained from interviews with informants; (2) Secondary data, in the form of Pucung Village population data. Meanwhile, data analysis was carried out by utilizing Qualitative Analysis Techniques. The results of this study indicate that: First, the activity "Leadership Training Based on Agrarian Resources for Pucung Village Government Office Staff" was carried out based on the idea, that Pucung Village Government Office staff need to understand and support the implementation of the master plan in various development activities; Second, the implementation of the training began with an opening by the moderator, then continued with remarks by the Head of Pucung Village and presentations by resource persons. Furthermore, the training activities were filled with open discussions between the resource persons and the participants, then ended with the closing of the event by the moderator. Third, Pucung Village Government Office staff interpret leadership as a skill or a management function in a person, which is used to influence, motivate, and direct others to do certain things in order to achieve certain goals. the implementation of the training began with an opening by the moderator, then continued with remarks by the Head of Pucung Village and presentations by resource persons. Furthermore, the training activities were filled with open discussions between the resource persons and the participants, then ended with the closing of the event by the moderator.